CONOCIMIENTOS Y PRÁCTICAS SOBRE PREVENCIÓN DE LA ANEMIA FERROPÉNICA EN MADRES DE NIÑOS MENORES DE 5 AÑOS EN EL PUESTO DE SALUD SAGRADA FAMILIA – SAN JUAN DE LURIGANCHO – LIMA - 2021 - Bustamante Ruiz, Rocio (2022)
The present research work entitled "Knowledge and practices on the prevention of iron deficiency anemia in mothers of children under 5 years of age at the Sagrada Familia health post in the San Juan de Lurigancho district", aims to analyze the relationship between knowledge and practices on the prevention of iron deficiency anemia in mothers of children under 5 years of age at the Sagrada Familia health post in the San Juan de Lurigancho district, Lima - 2021. The importance of the study lies in the problem How is knowledge related to the practices on the prevention of iron deficiency anemia in mothers of children under 5 years of age at the Sagrada Familia health post in the San Juan de Lurigancho district, Lima - 2021? so that mothers of children under 5 years of age have a better understanding of iron deficiency anemia. The research was developed methodologically, it is of an applied type, with a descriptive and correlational level. The design is non-experimental, cross-sectional, with a population of 671 mothers of children under 5 years of age from the Sagrada Familia health post in the San Juan de Lurigancho district, from which 196 mothers were drawn as a sample. The applied technique was the survey and the collection instrument was the data questionnaire for statistical processing with the SPSS 25; hypothesis testing was carried out using Spearman's correlation coefficient. It was concluded that there is no relationship between knowledge and maternal practices on iron deficiency anemia in mothers of preschool children from the Juan Pablo II human settlement in the San Juan de Lurigancho district, Lima - 2021, where the results were (rho = 0.069; Sig. = 0.338). Between the knowledge and maternal practices on iron deficiency anemia in mothers of preschool children of the Juan Pablo II human settlement of the San Juan de Lurigancho district, Lima - 2021. Therefore, the hypothesis and the general objective of the study were determined. Key words: Anemia knowledge, Anemia practices, Iron deficiency anemia.